1975
DOI: 10.1111/j.1432-1033.1975.tb04032.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Role and Mode of Operation of the Very‐Lysine‐Rich Histone H1 (F1) in Eukaryote Chromatin

Abstract: Proton magnetic resonance, circular dichroism and other studies of whole and cleaved calf thymus histone H1 (formerly F1) reveal the presence of specific folded structures in the region approximately from residue 40-115. Ionic, hydrogen-bond and hydrophobic interactions all appear to contribute to the stability of the structure, which is predicted to contain a-helices in regions 42-55 and 58-75. No evidence was found for 8-structures, either inter or intramolecular, or for any structure formation outside the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(61 citation statements)
references
References 17 publications
8
53
0
Order By: Relevance
“…Solubilized linker histones change their tertiary structure, and the charged tails obtain a random coil conformation (72). The final structure of linker histones in vivo is probably achieved only after binding to chromatin (73), and it may not be possible to retrieve completely this structure after reconstitution in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Solubilized linker histones change their tertiary structure, and the charged tails obtain a random coil conformation (72). The final structure of linker histones in vivo is probably achieved only after binding to chromatin (73), and it may not be possible to retrieve completely this structure after reconstitution in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies on H 1 have already been published [23,24]. Hydrodynamic studies have shown that H 5 does not aggregate at high ionic strength [8,28] and thereby resembles H 1 and not the remaining four histone fractions.…”
mentioning
confidence: 96%
“…There is at present no evidence to suggest why H 1 should be replaced in large part by H 5 and the present structural investigation of H 5 was carried out to point out the similarities and differences between H 5 and H 3 . Related studies on H 1 have already been published [23,24].…”
mentioning
confidence: 99%
“…RP-HPLCpurified histones exhibit a similar spectrum, but the molar ellipticities at 222 and 208 nm have been significantly reduced. Since it is possible to estimate the α-helical contribution to the spectrum from the ellipticity at 222 nm [33], we estimated that the reduction on the ellipticity at 222 nm represents a decrease of 15 % in the overall α-helix context of these histones. These alterations in the secondary structure are most probably responsible for the anomalous association pattern of these histones.…”
Section: Rp-hplc Prevents the Correct Association Of Histones Into A mentioning
confidence: 99%